Takwil of Ten Angels in View Islamic Mysticism (Analytical Study of the "Saderiah" Islamic Mysticism About Understanding Ten Angels in Karang Semanding Village, Kec. Balung, Kab. Jember) - Barmawi, Mohamad Barmawi (Advances in Humanities and Contemporary Studies, 2022)
The doctrine that emerges in the theology of Ahlussunnah Asy'ari  and Maturidi is the necessity of all mukallaf to believe in ten Angels, starting from the Angel Gabriel to Ridlwan. conceptually doctrine, belief about angels is part of the ghaybiyyat. Saderiah's mystical Islamic group is present in the midst of the classical understanding of Angel. According to this group, there's no way someone would have true faith when unable to understand the concept of angels in detail. Therefore understanding it is a must.This paper is a description of the results of the research that has been carried out by the author about tawil ten Angels according to "Saderiah" is part of mystic Islam, based on this research, it can be concluded that, according to "Saderiah" Angels are not creatures of God who are supernatural, but only symbols of human behavior alone. And in this group's belief, whoever is able understand the concept of Angels perfectly, surely he will become a calm figure, will even be able to protect life surrounding. Key Word Saderiyeh, Islamic Mysticism, Angels.